Advances in coal utilization technology : symposium papers presented May 14-18, 1979, Louisville, Kentucky - Vorres, Karl Spyros; Waterman, Wendell W.; Institute of Gas Technology (Chicago, Ill. : The Institute, 1979)
This symposium was intended to be similar in scope and treatment to the earlier Clean Fuels Fro Coal symposium sponsored by IGT in 1973 and 1975.
Includes bibliographies.
SJU
Loans
Keywords: Coal